ANALYSIS OF SMOKING CESSATION EFFORTS IN COFFE STALLS CUSTOMERS IN BANDA ACEH IN 2019 - Azzati, Rahmil; Hermasnyah, Hermasnyah; Saputra, Irwan; Nurjannah, Nurjannah; Adamy, Aulina (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: Smoking is a major risk factor against the burden of disease in the world. The large number of coffee stalls found in Banda Aceh is one of the causes of the high number of smokers, so it shows that coffee and cigarettes are inseparable. The purpose of this research is to find out the factors that affect smokers in stopping smoking habit in the coffee shop in Banda Aceh in 2019. Methods: This research is analytical observational, using Cross Sectional design. The research site at coffee shops in Banda Aceh was conducted in August 2019. The samples in this study were active smokers. The data was analyzed with a logistic regression test using Stata 13. Result: The results showed that the percentage of respondents who mad efforts to quit smoking was 72.19%. Bivariate analysis shows that there is a link between the number of cigarettes per day that is heavy (p=0.003), medium (p=0.005) and severe (p=0.026) with smoking cessation efforts, while the variable age, the first age of smoking, marital status, income, education, anxiety, alcohol consumption, knowledge, smoking time lag in the morning, and other smokers influences in the family environment has no relationship with quitting smoking. Multivariate analysis shows that the association to quitting smoking is in the in the variable number of cigarettes per day in the moderate, heavy, and severe categories. Conclusion: The most dominant variables that has a connection to smoking cessation is the heavy, moderate and severeamount of cigarettes per day.